Frequent NFKBIE deletions are associated with poor outcome in primary mediastinal B-cell lymphoma - Mansouri, Larry; Zenz, Thorsten (Blood, 2016)
We recently reported a truncating deletion in the NFKBIE gene, which encodes IκBε, a negative feedback regulator of NF-κB, in clinically aggressive chronic lymphocytic leukemia (CLL). Because preliminary data indicate enrichment of NFKBIE aberrations in other lymphoid malignancies, we screened a large patient cohort (n = 1460) diagnosed with different lymphoid neoplasms. While NFKBIE deletions were infrequent in follicular lymphoma, splenic marginal zone lymphoma, and T-cell acute lymphoblastic leukemia (<2%), slightly higher frequencies were seen in diffuse large B-cell lymphoma, mantle cell lymphoma, and primary central nervous system lymphoma (3% to 4%). In contrast, a remarkably high frequency of NFKBIE aberrations (46/203 cases [22.7%]) was observed in primary mediastinal B-cell lymphoma (PMBL) and Hodgkin lymphoma (3/11 cases [27.3%]). NFKBIE-deleted PMBL patients were more often therapy refractory (P = .022) and displayed inferior outcome compared with wild-type patients (5-year survival, 59% vs 78%; P = .034); however, they appeared to benefit from radiotherapy (P = .022) and rituximab-containing regimens (P = .074). NFKBIE aberrations remained an independent factor in multivariate analysis (P = .003) and when restricting the analysis to immunochemotherapy-treated patients (P = .008). Whole-exome sequencing and gene expression profiling verified the importance of NF-κB deregulation in PMBL. In summary, we identify NFKBIE aberrations as a common genetic event across B-cell malignancies and highlight NFKBIE deletions as a novel poor-prognostic marker in PMBL.